The Role of Teacher Leaders in the Implementation of the Merdeka Curriculum: A Case Study at SMPN 03 Soreang - Fanny Shofia Afifah; Lalan Sahlani; Daerobby Daerobby (UIN Sunan Gunung Djati Bandung, 2025)
The Merdeka Curriculum introduces a paradigm shift toward learner-centered education. As the vanguard of educational transformation, Guru Penggerak face the challenge of integrating the new curriculum with established practices. This study aims to analyze the role of Guru Penggerak in implementing the Merdeka Curriculum, their strategies for motivating colleagues, as well as the supporting and hindering factors. This qualitative study with a descriptive approach was conducted at SMPN 03 Soreang, Bandung Regency. Data were collected through in-depth interviews with five Teacher Leaders, participatory observation, and document analysis. The results indicate that Teacher Leaders serve as agents of curriculum integration, facilitators of paradigm shifts, and catalysts for professional collaboration. Effective strategies include a personalized persuasive approach, the sharing of best practices, and continuous training through the Merdeka Mengajar Platform. Key supporting factors are adaptive school leadership and budget allocation, while barriers include teacher resistance to change and limitations in technological resources. This study concludes that the success of the Merdeka Curriculum is largely determined by the capacity of Teacher Leaders to bridge policy with classroom practice through collaborative leadership